MONITORING OF THE NOISE LEVEL GENERATED WHEN THE MILLING OF REINFORCED CONCRETE PREFABRICATES AT MACOFIL S.A. TÂRGU JIU - Emil Catalin SCHIOPU; Madalina DRACEA (Fiabilitate şi Durabilitate)
The paper presents the results of monitoring the noise level generated by precast concrete manufacturing equipment. The paper presents an analysis of the results obtained following the performance of noise measurements compared to the maximum limit allowed by the environmental legislation in force.